Innovative Approaches for Determining the Needs of Education - Mironova, Nadya (Research Papers, 2010)
Modern management practice is based on the idea that continuous improvement of technical skills, theoretical knowledge and predisposition to cooperation between employees through training are essential for the promotion of an innovation process. An adequate system for determining training needs saves unnecessary costs, motivates employees and makes the cost of training reasonable and justified from management’s point of view. Therefore, determining the need for training is not just the first stage of the process of systematic training of human resources, but also a key factor for its effectiveness.In the context of assessing training impact, the need for the development of methodologies for vocational training assessment is steadily growing in significance. The purpose of this article is to improve the assessment of the need for continuing vocational training. The article includes three main section. The first section presents a conceptual framework of continuing education in organizations. In the second section innovative approaches to assessing the need for further training are examined. The third includes synthesized algorithms and evaluation of alternative methods for determining the need for training. The article concludes with the analysis and recommendations on the feasibility of innovative practices to assess the need for training in Bulgarian conditions.